2004
DOI: 10.1523/jneurosci.0178-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Forms of Long-Term Potentiation and Long-Term Depression Converge on a Single Interneuron in the Leech CNS

Abstract: Long-term potentiation (LTP) of synaptic transmission was observed in two types of synapses that converge on the same postsynaptic neuron in the leech CNS. These synapses were made by identifiable sensory neurons, the mechanosensory touch (T-) and pressure (P-) cells, onto the S-cell, an interneuron critical for certain forms of learning. Changes in both the T-S and P-S synapses appear to be activity dependent because LTP was restricted to inputs that had undergone tetanization; however, properties of synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
39
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 68 publications
(79 reference statements)
5
39
1
Order By: Relevance
“…This pattern of homLTP and hetLTD (synapses consisting of different presynaptic cells, but the same postsynaptic target) has been observed in the CA1 (Lynch et al, 1977), CA3 (Kosub et al, 2005) and dentate gyrus (Abraham and Goddard, 1983) regions of the hippocampus, the amygdala (Royer and Pare, 2003) and the visual cortex (Tsumoto and Suda, 1979). HomLTP at the T→S synapse is NMDAR-independent while T→S hetLTD is NMDAR-dependent (Burrell and Sahley, 2004). In this study, we examined underlying homLTP at the T→S synapse and discovered that inhibition of homLTP uncovered LTD in the same synapse that was apparently initiated in parallel with LTP in the tetanized pathway.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…This pattern of homLTP and hetLTD (synapses consisting of different presynaptic cells, but the same postsynaptic target) has been observed in the CA1 (Lynch et al, 1977), CA3 (Kosub et al, 2005) and dentate gyrus (Abraham and Goddard, 1983) regions of the hippocampus, the amygdala (Royer and Pare, 2003) and the visual cortex (Tsumoto and Suda, 1979). HomLTP at the T→S synapse is NMDAR-independent while T→S hetLTD is NMDAR-dependent (Burrell and Sahley, 2004). In this study, we examined underlying homLTP at the T→S synapse and discovered that inhibition of homLTP uncovered LTD in the same synapse that was apparently initiated in parallel with LTP in the tetanized pathway.…”
mentioning
confidence: 52%
“…However, it is now apparent that NMDAR-dependent signaling processes are not the only form of LTP operating in the brain (Malenka and Bear, 2004). Previously, we have observed that LTP in leech central synapses made by the touch mechanosensory neurons onto the S interneuron was NMDAR-independent (Burrell and Sahley, 2004). Here we examine the cellular mechanisms mediating T-to-S (T→S) LTP and find that its induction requires activation of metabotropic glutamate receptors (mGluRs), voltage-dependent Ca 2+ channels (VDCCs) and protein kinase C (PKC).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations